Kubhist 2: Falköpings Tidning 1860's - Språkbanken Text (University of Gothenburg, 2024)
Part of the collection Kubhist 2

Del av samlingen Kubhist 2
Kubhist 2: Falköpings Tidning 1860-talet
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik